BILL NO. HB 19 AMENDMENT NO. (FOR DRAFTERS USE ONLY) SENATE ACTION HOUSE ACTION (Tufts Archival Research Center, 2007)
Draft; Amendment to bill H.B. 19 stating that no restaurant can designate more than 65 percent of square footage as a smoking area.